Coordinator and Instructor - Manganaris, George A. (My University, 2026)
The training school was comprised of theoretical part [quality indicators, phytochemical parameters, determination of antioxidant capacity with different in vitro assays and advanced analytical procedures) and experimental part [(1)determination of soluble solids content, titratable acidity, stem removal force, tissue firmness (deformation force), skin penetration force, (2) extraction, total phenolic acid content determination, anthocyanin content determination, (3) antioxidant capacity determination (4) quantification of individual phenolic compounds and anthocyanins]